Design Quality Analysis of the Whispering Butterfly Robe as a Bridal Preparation Product - Sekar Wahyu Winingtyas; Irmayanti; Elmerillia Tsiampaca; Shofiyyah Nurul Mujahidah; Tasya Safrilla Nadhifa; Aulia Rizki Rahmawati; Nabila Alya Hanifah; Raymond Leonard (Universitas Negeri Semarang, 2026)
This study aims to analyze the design quality of the Whispering Butterfly Robe as a bridal preparation product. The robe was designed by adapting the characteristics of butterflies as the main source of inspiration, expressed through the application of organza floral appliqués and three-dimensional (3D) butterfly embellishments to create a feminine and elegant visual appearance. This study employed a descriptive quantitative method with an evaluative approach. The design quality assessment was conducted through expert judgment involving five fashion experts, including professors, educators, alumni, and fashion designers. The research instrument consisted of a validation sheet covering six evaluation aspects: design, sizing, sewing techniques, aesthetics, garment performance, and product uniqueness. The collected data were analyzed using descriptive statistics in the form of percentages. The results indicate that the Whispering Butterfly Robe achieved an average suitability score of 91.93%, categorized as “highly suitable.” The aesthetic aspect received the highest score (99.33%), followed by sizing (96.67%), garment performance (96.00%), and both design and sewing techniques (90.00%). Product uniqueness obtained a score of 79.33% and was categorized as “acceptable.” Overall, the findings demonstrate that the robe possesses high design quality and successfully integrates aesthetic value, functionality, comfort, and craftsmanship, making it suitable as a bridal preparation product.